The use of social referencing to teach safety skills to toddlers with autism. (9th November 2021) - Couger, Kathryn; Peterson, Pamela; MacDonald, Rebecca
Abstract: Social referencing is a chain of behavior where the presence of an ambiguous stimulus evokes a gaze shift from the stimulus to another individual. The other individual's facial expression signals either the availability of reinforcement or punishment. The purpose was to teach two toddlers with autism to discriminate between safe and dangerous stimuli through a social referencing chain. Participants were trained using differential reinforcement and least‐to‐most prompting to gaze shift from an item inside of a lunchbox or a bin to an adult, and to respond differentially based on the adult's facial expression. Results showed acquisition of both the discrimination between safe and dangerous stimuli and the maintenance of a social referencing chain in the presence of unfamiliar stimuli. These findings are discussed as they relate to the implications of teaching socially valid safety skills to toddlers with autism.